Perceived need of, and interest in, HIV pre-exposure prophylaxis amongst men who have sex with men attending three sexual health clinics in London, UK. (April 2018) - Bull, Lauren; Dimitrijevic, Pavle; Beverley, Sophie; Scarborough, Alex; Mandalia, Sundhiya; Dosekun, Olamide; Barber, Tristan; Reeves, Iain; McCormack, Sheena; Rayment, Michael
HIV pre-exposure prophylaxis (PrEP) has proven efficacy in reducing the risk of HIV infection in men who have sex with men (MSM), but has not yet been commissioned in the UK. The aim of this study was to investigate perceived need and benefit (or experience of) PrEP among HIV-negative MSM attending sexual health clinics. HIV-negative MSM attending three sexual health centres in London, UK were opportunistically invited to complete a questionnaire. Data collected comprised demographic data and sexual and drug use behaviours as well as questions regarding perceptions of risk and need for PrEP. Logistic regression analysis was undertaken to identify variables predicting acceptability of, and intention to use, PrEP. In addition, data were gathered in respondents already taking PrEP. Eight hundred and thirty-nine questionnaires were analysed. The median age of respondents was 35 years (IQR 28–41, range 18–78), 650 (77%) were of white ethnicity and 649 (77%) had a university education. Four hundred and fifty-six (54%) reported at least one episode of condomless anal sex in the preceding three months, 437 (52%) reported recreational drug use in the preceding three months and 311 (37%) had been diagnosed with a sexually transmitted infection within the preceding six months. Four hundred and sixty-three (64%) of 726 strongly agreed with the statement 'I think I would benefit from PrEP'. Multivariate logistic regression analysis demonstrated that having receptive anal intercourse (RAI) without condoms, having an awareness of the risk of unprotected RAI and having belief in the effectiveness of PrEP were independent predictors for someone thinking they would benefit from taking PrEP. Eight percent of respondents (59/724) had already taken or were currently taking PrEP. The results suggest that individuals at risk are likely to perceive themselves as benefiting from PrEP. The majority perceived their risk of acquiring HIV and benefit from PrEP accurately. Overall they appeared to have little concern over the use of PrEP and generally positive attitudes. Further investigation is warranted to understand why those at risk do not perceive benefit from PrEP.